Pengaruh Kepemimpinan Etis dan Etos Kerja terhadap Kinerja Guru pada SMK Negeri 1 Baso - Marsela Marsela; Imran Imran; Sabri Sabri (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the Influence of Ethical Leadership and Work Ethic on Teacher Performance at SMK Negeri 1 Baso. The population in this study was all teachers at SMK Negeri 1 Baso, numbering 53 people, and at the same time became the sample in this study by using a census or saturated sample method with a sample size equal to the population, which is 53 sample respondents. Data were collected through the distribution of questionnaires with a Likert scale model then tested for the validity and reliability of the questionnaire. The data analysis technique used is the Multiple Linear Regression method. The results of this study are a). Ethical Leadership (X1) has a positive and significant effect on Teacher Performance at SMK Negeri 1 Baso partially. b). Work ethic (X2) has a positive and significant effect on Teacher Performance at SMK Negeri 1 Baso partially. Ethical Leadership and Work Ethic together (simultaneously) have a positive and significant effect on Teacher Performance at SMK Negeri 1 Baso can be seen from the results of the f test. The results of the determinant coefficient test show that the ethical leadership and work ethic variables make a large contribution to Teacher Performance at SMK Negeri 1 Baso.